THE ANALYSIS EUPHEMISM MEANING IN DIFFERENT GENRE TEXTS - Good Sumbayak Lingga; Rahmadsyah Rangkuti (Universitas Bengkulu, 2021)
The euphemism in texts of different genre is the most focused on this research. Because of nowdays mass media are no longer censor or even selected the material that they served to public although it is too harsh. and The using of euphemism itself are also lower and lower from years to years. Thought there are a few words can’t be spoken cause the words are too taboo to spoken. that’s why the writer choose to analysis this euphemism in different texts. The method of this research used qualitative research to analized the data from written text. The instrument of this thesis was document analysis. The subject of the study were fiction and non-fiction texts (Sir Erich Segal’s novel, Love Story. Short story of Ashley Marks,Eighth Moon. And scientific articles ,Now You See It, Now You Don’t by Paula McGee. Forced Marriage And Health by Asma Ashraf).After collecting the data , the writer finds out only 8 types of euphemism used in the texts above and fiction texts(novel & short story) uses euphemism more than non-fiction text. because it shows the skill and techniques of writing and speaking in literature, while non-fiction texts (scientific articles) only use few of euphemism, because the contain of text talking about science, knowledge, technology and even about reality. So, the words used in scientific articles must clear and show the meaning directly although it is rather harsh. That means for the reader or the audience do not misunderstand the contain of the texts.